Chrysophanol Relieves Cisplatin-Induced Nephrotoxicity via Concomitant Inhibition of Oxidative Stress, Apoptosis, and Inflammation - Ma, Siqing; Xu, Heng; Huang, Weihua; Gao, Yongchao; Zhou, Honghao; Li, Xiong; Zhang, Wei (Frontiers in Physiology, 2021)
Cisplatin (DDP) is one of the most frequently prescribed chemotherapy medications. However, its nephrotoxicity which often leads to acute kidney injury (AKI), greatly limits its clinical application. Chrysophanol (CHR), a mainly active anthraquinone ingredient, possesses various biological activity and pharmacological activity. In this study, we aimed to investigate the underlying protective mechanisms of CHR against DDP-induced acute kidney injury (DDP-AKI) by using C57BL/6 mice and human proximal tubule epithelial cells. In vivo, we found that pre-treatment with CHR greatly relieved DDP-AKI and improved the kidney function and morphology. The mechanistic studies indicated that it might alleviated DDP-AKI by inhibiting oxidative stress, apoptosis and IKKβ/IκB𝛂/p65/NF-κB inflammation signaling pathway induced by DDP. Moreover, we found that the cell viability of HK2 cells reduced by DDP was partially rescued by CHR pre-incubation. Flow cytometry results further indicated that CHR pre-incubation suppressed DDP induced cellular ROS generation and inhibited cell apoptosis in a dose-dependent manner. In summary, our results suggested that CHR might be a novel therapy for DDP-induced acute kidney injury.